Physical and Organoleptic Qualities of Milk-Based Caramel with Variations in Addition of Pineapple Fruit (Ananas comosus (L) Merr.) - D. L. Rukmi; M. N. A. Muslim; E. C. Wulandari; S. Mulyani; A. M. Legowo (Jurnal Sain Peternakan Indonesia, 2021)
The purpose of this study was to determine the physical and organoleptic qualities of milk-based caramel with variations in the use of pineapple (Ananas comosus (L) Merr.). The design of this study used a completely randomized design (CRD) with five treatments and four replications. The tested treatments include milk-based caramel, which was processed with pineapple juice at T0=0%; T1=5%; T2=10%; T3=15%; T4=20%. The research variables included physical quality testing consisting of water content and crude fiber content, further testing of texture, color, and panelists' preference as organoleptic parameters tested using sensory tests. The observations obtained will be processed using analysis of variance (ANOVA) with a level of 5% and will be further tested using Duncan's Multiple Range Test (DMRT) if it shows a significant effect. Based on the results of analysis of variance (ANOVA), the variation in various treatments with the addition of pineapple fruit in the milk-based caramel processing showed a significant effect (P<0.05) on the physical quality of caramel (crude fiber content and water content) and organoleptic quality (texture, color), and preference) on milk-based caramel products. The percentage of crude fiber content is 0.35%-4.50%; moisture content 10.15%-15.63%; texture score is hard to not hard; the color score is light brown to brown and liking score is slightly like to like. The conclusion of this research was the addition of pineapple affects crude fiber content, milk caramel water content, texture, color, and milk caramel preference.